The legal status of the subjects of inheritance under the law in the Republic of Kazakhstan and the Republic of Turkey: a comparative legal analysis - Nukusheva, A.A.; Aktay, A.N.; Erdogan, Y. (Bulletin of the Karaganda University “Law Series”, 2022)
In the context of actively developing relations between the Republic of Kazakhstan and the Republic of Turkey, the issues of regulating the legal status of subjects of inheritance by law are of particular relevance. Due to the peculiarities of national, historical, religious, cultural and family traditions, inheritance relations complicated by a foreign element are among the most difficult in legal regulation. According to the authors, the study and analysis of the legal status of subjects of inheritance under the law seems to be so significant, because due to active migration processes between the two countries, many citizens of Kazakhstan and Turkey have relatives in these countries, and, accordingly, inherit after them under the laws of another state. A comparative legal analysis of the current inheritance legislation in the field of regulation of the legal status of inheritance under the legislation of the Republic of Kazakhstan and the Republic of Turkey showed significant differences in the legislative regulation of subjects of in-heritance under the legislation of the two countries. Based on a comparative legal analysis of the current legislation of the Republic of Kazakhstan and the Republic of Turkey, a number of differences were identified in the order of precedence, the spouse’s share in the inherited property and the policy of taxation of inherited property. At the same time, there are also general approaches to determining the hereditary status and to determining the status of the testator. In practical terms, this study is of interest to lawyers practicing in the field of inheritance law, as well as private international law.